2017
DOI: 10.1016/j.scr.2016.12.020
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29 impairs the early phase of reprogramming process by targeting active DNA demethylation enzymes and Wnt signaling

Abstract: Somatic cell reprogramming by transcription factors and other modifiers such as microRNAs has opened broad avenues for the study of developmental processes, cell fate determination, and interplay of molecular mechanisms in signaling pathways. However, many of the mechanisms that drive nuclear reprogramming itself remain yet to be elucidated. Here, we analyzed the role of miR-29 during reprogramming in more detail. Therefore, we evaluated miR-29 expression during reprogramming of fibroblasts transduced with len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 60 publications
2
13
0
1
Order By: Relevance
“…Overexpression of miR-29a was correlated to reduced levels of Slit glycoprotein 2 (SLIT2) and its receptor Roundabout 1 (ROBO1) which, in turn, resulted in inhibition of mesenchymal stem cell viability and proliferation [78]. Moreover, it was shown that transfection of miR-29 family members at an early stage of somatic cell reprogramming may decrease the number of colonies expressing pluripotent markers, such as Oct4 [79]. These results may explain the mir-29a-3p expression profile observed in EqASC EMS treated with metformin.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of miR-29a was correlated to reduced levels of Slit glycoprotein 2 (SLIT2) and its receptor Roundabout 1 (ROBO1) which, in turn, resulted in inhibition of mesenchymal stem cell viability and proliferation [78]. Moreover, it was shown that transfection of miR-29 family members at an early stage of somatic cell reprogramming may decrease the number of colonies expressing pluripotent markers, such as Oct4 [79]. These results may explain the mir-29a-3p expression profile observed in EqASC EMS treated with metformin.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, contrasting findings arising from different methods used were previously pointed out by our group in the study of the miR-29 family. Using transfection of synthetic miRs or inhibitors, our group and others showed that miR-29a hampers reprogramming by different mechanisms, including activation of WNT/beta-catenin signaling (by targeting GSK3B) and targeting of active DNA demethylation enzymes of the TET family [71, 78, 79]. Strikingly in contrast, expression of miR-29 throughout the process using a retroviral vector promotes reprogramming, an effect resulting from passive global demethylation following constitutive knockdown of the targets Dnmt3a and Dnmt3b [80].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these conflicting results, and also based on a work from our group, which identified Tet1, 2, and 3 (components of active DNA demethylation) as targets of miR-29 [118], we further explored miR-29’s role in reprograming using synthetic miRs and anti-miRs. We showed that by targeting Tet1, 2, and 3 and Gsk3-beta (the phosphatase involved in B-catenin degradation), miR-29a hampers reprograming, likely by interfering with hydroximethylation and by activating Wnt signaling, respectively [119].…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%